Contrato, repersonalização e constituição: a concretização da dignidade da pessoa humana pelo princípio da boa-fé objetiva - Tonial, Nadya Regina Gusella (Universidade do Vale do Rio do Sinos, 2007)
The present study constitutes in an analysis of the principle of the objective good-faith in contracts, on the basis of the biggest value of the dignity of the human being, from a dimension of ethicism brought up by the Democratic State of Right. The Great Letter promoted the constitucionalization of the law spreading its effect on the legal system. As a consequence the repersonalization of the civil law allowed human being to raise to the center of the system. In the contractual law, along with the autonomy of the will, the lines of direction of the sociability, the fairness and the ethicism through respectively, the principles of the social function, its economical balance and the good-faith objective. Because of the repersonalization, the pact started to contain a social utility and to represent a way of promote the guardianship of the confidence, protecting the legitimate expectations of the parts. However, great part of the applicators of the right continues related to a liberal-individualist model that
Keywords: boa-fé objetiva; dignidade humana; direito contratual; fenomenologia; repersonalização; princípio constitucional; Ciências Sociais Aplicadas